Options on futures : a hands-on workbook of market proven-trading strategies - Frost, Ronald J. (London : McGraw-Hill, 1989)
Extreme care has been taken in this workbook to take a complex subject and make it understandable to any trader. Options are not for everyone. But those who are financially and psychologically fit to trade options need to know several factors to help them make decisions
Includes index.
osc 11/07/2018
Loans
Keywords: Stock options; Financial futures